Penafsiran Ayat Ayat Ibadah Dalam Al-Qur’an (Sedakah, Haji Dan Umrah, Wakaf) - Elsa Alfaiza Rahmadani; Nayla Afita; Maryam Dewi Tsaniyah; Edi Hermanto (CV. ITTC INDONESIA, 2025)
Worship in Islam plays a crucial role in regulating human relations with Allah SWT while also shaping social life and community ethics. In practice, worship is often understood as a mere ritual activity, thus under-emphasizing the social and humanitarian values ​​it embodies. This article aims to analyze the interpretation of Quranic verses related to charity, the Hajj and Umrah pilgrimages, and waqf (endowments), in order to gain a more comprehensive understanding of the meaning and function of worship in Islam. This research uses a qualitative approach with library research methods, using data sources in the Quran, classical and contemporary commentaries, and relevant Islamic literature. The results indicate that charity serves as a means of purifying the soul and strengthening social solidarity, the Hajj and Umrah contribute to the development of piety, self-control, and brotherhood among the people, while waqf is a form of sustainable financial worship oriented towards the public good. Thus, worship in the Quran is not merely ritualistic but also serves as an ethical and spiritual foundation for individual and social life